Pemanfaatan Limbah Kulit Udang Asal Sampah Rumah Tangga Sebagai Pupuk Organik Cair (POC) di Daerah Rawamangun - Irnidayanti, Yulia (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
Shrimp waste is one of the household waste products that has prospects as a liquid organic fertilizer (POC). The content of the macronutrient CaCO3 plays an important role in plants. Making organic liquid fertilizer can overcome odour problems that may arise due to the presence of this waste in the environment. The society service methodology used counselling and training to create POC for residents and business opportunities. Community service activities were carried out at RW 03 Rawamangun, the number of respondents was 12 people, carried out by lecturers and students of the Biology Study Program-Jakarta State University. Counselling and training on making POC from shrimp waste in RW 03 Rawamangun was able to increase participants' standing by up to 83%. The results of the training activities produced a liquid organic fertilizer product packaged in 300 mL bottles which is useful as plant fertilizer in the household. POC products can also be sold as additional income. Conclusion: P2M activities need to be carried out in a sustainable manner and help the government to overcome the problem of household waste that smells bad.